Y-PSZ/Bioglass 45S5 composite obtained by the infiltration technique of porous pre-sintered bodies using sacrificial molding (Research, Society and Development, 2021)
The aim of this work was to obtain porous ceramic parts based on Zirconia stabilized with 5mol.% Yttria (5Y-PSZ), suitable for the infiltration with bioactive glasses, using 3D printed sacrificial polymeric molds. In a first step, honeycomb structured molds were designed with the SolidWorks® software and manufactured by 3D printing using polylactic acid filaments (PLA). These molds were filled with a ceramic mass composed of 5Y-PSZ nanoparticles containing 3wt% polymeric binder and consolidated under pressure of 10MPa and then sintered at 1200 °C-30 min the polymeric molds were consumed. The obtained hexagonal-shaped, porous 5Y-TZP bodies were infiltrated with the bioactive glass 45S5, calcium sodium phosphosilicate, at 1350 °C. The materials were characterized by their relative density, their phase composition by X-ray diffraction analysis, and their microstructure by scanning electron microscopy (SEM-EDS), besides their mechanical properties of hardness and fracture toughness. Pre-sintered 5Y-PSZ substrates exhibit relative density around 75%, and 90% after sintering and Bioglass infiltration. The samples' microstructure is composed of a 5Y-PSZ matrix of sub-micrometric zirconia grains with an average size of 1.0 mm, besides the secondary infiltrated glassy phase homogeneously distributed, with a Ca/P ratio of 1.7, close to the ideal proportion for hydroxyapatite formation. In conclusion, sacrificial molding is an interesting route to obtaining dense Y-PSZ/Bioglass 45S5 composite in a honeycomb format.